Improvement of fatigue life by compliant and soft interlayers. (1st March 2016) - Kolednik, O.; Zechner, J.; Predan, J.
Abstract: Retardation of fatigue crack growth rate due to the introduction of thin, compliant and/or soft interlayers is investigated. The mechanism is the reduction of the crack driving force in the interlayer. Fatigue tests are conducted on composites made of high-strength aluminum alloy as matrix and technically pure aluminum or adhesive as interlayer material. The adhesive interlayer causes an increase in fatigue life by a factor 20 or more, whereas the aluminum interlayer yields only a moderate improvement. Numerical simulations based on the configurational force concept are utilized for understanding. The results show new possibilities for the design of fatigue-resistant materials. Graphical abstract: